Generation of 2n series fractional factorial plans robust against linear-trend - SARKAR, SUSHEEL KUMAR; LAL, KRISHAN; DASH, SUKANTA; YADAV, SUNIL KUMAR; HIMANSHU (The Indian Journal of Agricultural Sciences, 2021)
Trend-free design for single factor at two level factorial experiments (complete and fractional both) are available in literature but trend-free multi-factor design could not be traced in the literature. There are a number of experiments in agronomy, agricultural engineering and virology where factors are multi-level. Multi-level factorial/fractional factorial designs are not readily available, and there is a need to address this problem. Hence an attempt has been made to construct linear trend-free multi-level factorial/ fractional factorial main effect design with their cost consideration.